PELATIHAN PEMBUATAN SABUN CUCI PIRING CAIR UNTUK MASYARAKAT KAMPUNG BENAR DUSUN VI DESA KOTA PARI, KECAMATAN PANTAI CERMIN, KABUPATEN SERDANG BEDAGAI - Lisa Dwi Afri; Annisa Ul Khoiriah Pasaribu, Fadhilah Rahmah, Mukhlida Khofipah Hasibuan, Nurhalimah, Widya Putri Ma (JOURNAL OF COMMUNITY DEDICATION, 2023)
The lack of activities for women in Kampung Benar Dusun VI made us want to conduct training on making liquid dishwashing soap, with this activity the community can find out more about liquid dishwashing soap products. Especially for housewives, now it has become a daily necessity. By making your own liquid washing soap that is good and cheap to use or sell every day, the price of washing soap products can be reduced. Liquid dish soap dissolves more easily and works better in water, so many people prefer to use liquid dish soap rather than cream. This is what made us conduct training in the Kampung Benar area, Dusun VI, Kota Pari Village. The aim of this training is to gain an understanding of making liquid soap and to gain knowledge or skills to be able to use it in life, to be able to help in making liquid soap and to gain practical skills. People can also use this work as additional work in areas where they are not productive in income-generating activities. The hope is that it can encourage people to develop their own businesses, so that they can build an independent society. The methods used in Social Work are PAR (Participatory Action Research), discussions and soap making demonstrations. Divided into three stages, namely preparation, evaluation and implementation, this project. The raw materials used include Texapon, NaCl, SLS, Foamboster, Perfume, Green Dye. The resulting water washing soap produced in this project is 15 liters with a thick body, green color and lemon smell. We hope that the people of Kampung Atas Dusun VI Pari City can learn how to make liquid soap through this activity. Making liquid dishwashing soap is a simple process that we can do ourselves, and can be used as a side project at home. People can save money by buying commercial washing soap because the price of homemade washing soap is cheaper and there are many homemade soap products available. From making dishwashing soap, 25 600 ml plastic bottles were produced. The conclusion that can be drawn from this Community Service activity is that the training in making water-washing soap in Kampung Benar Dusun VI, Kota Pari Village was carried out well and smoothly.